1956
DOI: 10.1063/1.1722464
|View full text |Cite
|
Sign up to set email alerts
|

Stress Analysis in Viscoelastic Materials

Abstract: The problems of stress analysis for linearly viscoelastic materials are considered. This is the simplest group of materials which exhibit the general stress-strain characteristics found in polymers and plastics. Three basic aspects are considered: measurement of material properties, determination from these of the operator equations between stress and strain or equivalently of the viscoelastic model, and use of this in the theoretical analysis of stress distributions. Quasi-static analysis, in which inertia fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1960
1960
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Theoretical described of (Liping and Chongyin, 1985;Gupta and Pandya, 1966;Lee 1956;Dey and Basudhar, 2010;Abubakar et al, 2010): Visco-elastic body of stress and strain analysis and the general media as a row, according to the same basic equation. The difference only lies in the different stress-strain relationship.…”
Section: Rheological Model Of Paddy Field Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical described of (Liping and Chongyin, 1985;Gupta and Pandya, 1966;Lee 1956;Dey and Basudhar, 2010;Abubakar et al, 2010): Visco-elastic body of stress and strain analysis and the general media as a row, according to the same basic equation. The difference only lies in the different stress-strain relationship.…”
Section: Rheological Model Of Paddy Field Soilmentioning
confidence: 99%
“…Science Publications China's GM rice paddy soil rheological model, the rheological equation (Gupta and Pandya, 1966;Lee, 1956):…”
Section: Calculation Of Rheological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of solution employed in such problems rests on the use of the Laplace transform (to eliminate the dependence on time), and the correspondence principle-between the field equations and boundary conditions in the linear theories of homogeneous and isotropic elasticity and viscoelasticity-which, in the absence of thermal effects, has been established for incompressible media by Alfrey [1], and in general form by Lee [2], The extension of Lee's analogy to problems involving time-dependent temperature fields has been very recently given by Sternberg [3]. Also, considerable attention has been given to oscillation and wave propagation problems of viscoelasticity in which the inertia terms have been included, e.g., [4,5,6], and additional references on the subject may be found in a recent survey by Lee [7], Closely related to the scope of the present investigation is the recent work on vibrations of thin shallow elastic shells by E. Reissner [8], who, by utilizing the linear differential equations due to Marguerre [9], has shown that for transverse vibrations of shallow shells the longitudinal inertia terms (with negligible error) may be omitted; and hence, the formulation of the elastokinetic problems of shallow shells, as in the case of elastostatics, may be reduced to the determination of axial (or transverse) displacement and an Airy stress function. Subsequently, E. Reissner [10] dealt with transverse vibrations of axisymmetric shallow elastic spherical shells, and in particular, obtained the solution for an unlimited shell due to an oscillating point load (varying harmonically in time) at the apex.…”
Section: Introductionmentioning
confidence: 99%
“…For such steady state solutions, it is more convenient to return to the viscoelastic solution (4.5) in the Laplace-Hankel transform-plane. Following Lee [6], we replace s by iu in all quantities except in p*(i, s) which is replaced by7 P*(£), and then take the inverse Hankel transform leading to the (real) steady state amplitude W(r) for the axial displacement. When p(r, t) is specified by (5.6a), through the process just described and with the aid of (4.14a), we obtain…”
Section: Introductionmentioning
confidence: 99%